2002
DOI: 10.1046/j.1442-200x.2002.01495.x
|View full text |Cite
|
Sign up to set email alerts
|

Fetal growth and the timing of exposure to maternal smoking

Abstract: Maternal smoking during any trimesters increased the risk of preterm birth. Maternal smoking during the third trimester reduced the body length of both full-term and preterm neonates, and the birthweight of the full-term neonate in a somewhat dose-dependent manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 10 publications
(19 reference statements)
2
18
0
Order By: Relevance
“…Because infant mean birthweight decreased to 2922 and 2911 g when women quit smoking during the second and third trimester, respectively, these women were grouped with women who smoked throughout pregnancy. This agrees with previous findings that quitting smoking early in pregnancy does not greatly affect infant birth size (25).…”
Section: Study Participantssupporting
confidence: 93%
See 1 more Smart Citation
“…Because infant mean birthweight decreased to 2922 and 2911 g when women quit smoking during the second and third trimester, respectively, these women were grouped with women who smoked throughout pregnancy. This agrees with previous findings that quitting smoking early in pregnancy does not greatly affect infant birth size (25).…”
Section: Study Participantssupporting
confidence: 93%
“…Additionally, the individual effect of smoking on birth size was analyzed because of its known impacts on fetal growth (25,28). The main linear regression model included mean infant birth size as the dependent variable, caffeine intake as a categorical variable, the CYP1A2 genotype (CC/CA vs. AA), and the CYP1A2 and caffeine gene-environment interaction variable (the product term of maternal caffeine intake and CYP1A2 genotype) adjusted by the confounders listed above.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…While there is some evidence that specific trimester effects occur in association with birth weight (Ohmi et al, 2002), it is important to note that one well-designed study (Toschke et al, 2003) found no significant increase in the odds ratios for childhood BMI in association with first trimester smoking versus smoking throughout pregnancy. At any rate, it appeared that women in the present study may not have been able to make distinctions by trimester accurately, requiring analyses of data for the entire pregnancy.…”
Section: Discussionmentioning
confidence: 98%
“…In some cases, the etiology of these disorders is already well known whereas in some other cases it is still under study. Poor or inadequate nutrition, smoking, alcohol abuse, lower genital tract infections, anemia, hypertension, gestational or non-gestational diabetes, obesity, metabolic and antiphospholipid syndromes, among others, are some of the maternal conditions that may have an effect on fetal growth [1][2][3][4][5][6][7][8]. These maternal disorders affect the environment where the fetus is developing and may produce metabolic, immune, vascular, hemodynamic and renal alterations [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%